2020
DOI: 10.2169/internalmedicine.5401-20
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Stiffness Is Associated with Coronary Microvascular Dysfunction in Patients with Non-obstructive Coronary Artery Disease

Abstract: Objective Associations between aortic stiffness and cardiovascular disease events are mediated in part by pathways that include coronary microvascular dysfunction (CMD) and remodeling. However, the relationship between aortic stiffness and CMD remains unclear. The present study aimed to determine whether aortic stiffness causes CMD as evaluated by the hyperemic microvascular resistance index (hMVRI) in patients with non-obstructive coronary artery disease (CAD). Methods The intracoronary physiological variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…A recent study showed that CAVI is one of the independent determinants of the hyperemic microvascular resistance index in patients with non-obstructive coronary artery disease, that is, it is associated with coronary microvascular dysfunction [ 11 ]. It was also shown a relationship of CAVI with the presence of obstructive coronary artery disease during CT angiography [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that CAVI is one of the independent determinants of the hyperemic microvascular resistance index in patients with non-obstructive coronary artery disease, that is, it is associated with coronary microvascular dysfunction [ 11 ]. It was also shown a relationship of CAVI with the presence of obstructive coronary artery disease during CT angiography [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study did not collect the data as to whether participants had LVH; however, it revealed that HMR was increased in the higher aortic PP group. Muroya et al also reported that aortic stiffness (assessed using the cardio-ankle vascular index) was an independent determinant of the invasive HMR index (β=0.25, p=0.007) 29. The high aortic PP group had a high ASCVD risk score and was more likely to have comorbidities such as DM, HTN and dyslipidaemia.…”
Section: Discussionmentioning
confidence: 93%
“…Muroya et al also reported that aortic stiffness (assessed using the cardio-ankle vascular index) was an independent determinant of the invasive HMR index (β=0.25, p=0.007). 29 The high aortic PP group had a high ASCVD risk score and was more likely to have comorbidities such as DM, HTN and dyslipidaemia. Although none of the patients had obstructive coronary disease, many patients may have minimal artery disease, and the high aortic PP group may more likely demonstrate minimal stenosis compared with patients with low aortic PP.…”
Section: Discussionmentioning
confidence: 96%
“…4,28,29 Aortic stiffness was demonstrated to be associated with coronary microvascular dysfunction in patients with nonobstructive coronary artery disease. 30…”
Section: Hypertension-mediated Organ Damagementioning
confidence: 99%